2023
DOI: 10.3389/fmicb.2023.1243811
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization supports causality between gut microbiota and chronic hepatitis B

Quanzheng Zhang,
Jinhua Zhou,
Xiaoxiao Zhang
et al.

Abstract: BackgroundObservational studies have provided evidence of a close association between gut microbiota and the progression of chronic hepatitis B (CHB). However, establishing a causal relationship between gut microbiota and CHB remains a subject of investigation.MethodsGenome-wide association study (GWAS) summary data of gut microbiota came from the MiBioGen consortium, while the GWAS summary data of CHB came from the Medical Research Council Integrative Epidemiology Unit (IEU) Open GWAS project. Based on the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The Genus Eubacterium ventriosum group is a component of the Family Lachnospiraceae . The Genus Ruminococcus gauvreauii group belongs to the Family Ruminococcaceae and is a component of the Phylum Firmicutes ( Zhang et al, 2023 ). The association between these two genera and DN has not been examined by conventional epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…The Genus Eubacterium ventriosum group is a component of the Family Lachnospiraceae . The Genus Ruminococcus gauvreauii group belongs to the Family Ruminococcaceae and is a component of the Phylum Firmicutes ( Zhang et al, 2023 ). The association between these two genera and DN has not been examined by conventional epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Holdemania sp900120005 belongs to Holdemania. Holdemania is a pathogenic bacterium that has been found in various environments and poses a potential threat to human health [41]. Studies have shown an elevated presence of Holdemania in in ammatory and psychiatric disorders, indicating its pathogenic nature [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an increase in both the Bilophila and Ruminococcaceae genera affects the reproductive performance of sows [45]. Chronic hepatitis B patients showed a correlation between an increase in the genus Holdemania and a heightened risk of chronic hepatitis B [46]. Elevated blood urea nitrogen levels in children with idiopathic nephrotic syndrome positively correlate with the Ruminococcaceae genus [47].…”
Section: Discussionmentioning
confidence: 99%